Power and status - Thye, Shane R.; Skvoretz, John (JAI, 2003)
Advances in Group Processes publishes theoretical analyses, reviews and theory based empirical chapters on group phenomena. Volume 20, the second volume of a five-series set, includes papers that address fundamental issues of power and status. Chapter one integrates social influence network theory with core ideas from affect control theory and the expectation states programme. The second chapter compares reciprocal exchange to negotiated exchange in terms of the power development, trust and perceptions of fairness. Chapter three examines the entire population of unique exchange networks up to size nine, giving predictions using power dependence theory and the resistance branch of network exchange theory. As a set, these chapters address major issues of power in social exchange relations. The next four chapters are aimed at important issues of status in groups.-Chapter four theorizes the complex connection between power and status, showing that power can produce status only if negative emotional reactions are mitigated. This analysis sheds new light on theories of collective action. Chapter five extends reward expectations theory by offering a new model of allocative behaviour, and comparing that model to previously collected data. The sixth chapter extends status construction theory to incorporate the effect of social identification. This new formulation is then tested and supported with data from thirty five dot-com organizations. The final two chapters incorporate theories of legitimacy to provide insights into power and status. Chapter eight reviews and explicates the basic principles of legitimacy in the Zelditch and Walker research programme. This paper traces the successes and failures of two dozen studies across several decades.-Finally, chapter nine uses legitimacy theory to resolve two anomalies in the status literature, one dealing with gender saliency and the other with the enactment of identity- versus status-related behaviours. Overall, the volume includes papers that reflect a wide range of theoretical approaches to power and status and contributions by major scholars that work in the general area of group processes.
Keywords: Power (Social sciences); Social status.; elektronické knihy; electronic books